Employee Performance Transformation through Organizational Culture and Communication Innovation at PT. Alam Jaya Karawang - Rohmah, Siti; Nandang, Nandang; Apriani, Zenita (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
The purpose of this study is to explore the impact of organizational culture and organizational communication on employee performance at PT Alam Jaya Karawang. This study uses a verification method with quantitative data analysis, distributing questionnaires as a data collection tool to employees of PT Alam Jaya Karawang. The findings in this study are that organizational culture has a partial influence on the performance of employees of PT Alam Jaya Karawang with a tcount value greater than the t valuetabel (18.696> 1.655). Organizational communication also has a partial influence on the performance of employees of PT Alam Jaya Karawang with a tcount value greater than the t valuetabel (12.731> 1.655). Simultaneously, organizational culture and organizational communication have an influence of 81% on the performance of employees of PT Alam Jaya Karawang while the remaining 19% can be attributed to other factors not examined in this study.